Would households understand average inflation targeting? - Mathias Hoffmann; Lora Pavlova; Emanuel Mönch; Guido Schultefrankenfeld (Deutsche Bundesbank, 2022)
Yes, they would. In a randomized control trial, we provide groups of respondents from the Bundesbank Online Panel Households with information about a hypothetical alternative ECB monetary policy regime akin to the Federal Reserve's flexible average inflation targeting (AIT). Inflation expectations significantly increase for the treated individuals. When provided with additional information about near-term inflation, individuals update their expected inflation path in line with the central banks' intentions. This is particularly true for individuals with high trust in the ECB. We assess the economic significance of our findings by comparing two model economies under different monetary policy strategies, calibrated to match the difference in medium-term inflation expectations from our survey results. Under AIT, inflation is substantially less volatile and the frequency of hitting the lower bound on interest rates is considerably reduced.
Keywords: F33; E31; E32; 330; Monetary Policy Strategy; Household Inflation Expectations; Randomized Control Trial; Survey Data